PENGARUH PELAYANAN PEMBUATAN E-KTP TERHADAP KEPUASAN MASYARAKAT STUDI KASUS DI KECAMATAN DRAMAGA KABUPATEN BOGOR - Sufryanthi, Sufryanthi; Kusnadi, Yahdi (LPPM Universitas Nusa Mandiri, 2016)
The creation of the e-ID CARD issued by the Government in this regard the Ministry of Interior gave the side the ease in making Residents Sign Cards (KTP) as official proof of identification for every citizen. The technique of data collection undertaken by way of ask a few questions or written statement to the respondent the owner or user of the e-ID CARD around the area of Kecamatan Dramaga, Bogor. From the analysis, the determination of the coefficient of 0,199 obtainable. 19.9% it means that the variable satisfaction celebrated influenced by quality of service, while the 80,1% community satisfaction variables affected by other variables that are not discussed in this study